The Effect of Quenching Intercritical Dual-Phase Heat Treatment on The Corrosion Behaviour of Reinforced Steel - Kelestemur, Oguzhan; Yildiz, Servet (Gazi Univ, 2008)
In this study, corrosion behaviour of dual-phase (DP) steel obtained with intermediate quenching heat treatment has been assessed in comparision to ferrite-perlite reinforced steel in concrete. Corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of steels embedded in concrete was measured every day for a period of 30 days in accordance with ASTM C 876 standard. In the second stage, anodic and cathodic polarization values of these steels were obtained and then the corrosion currents were determined with the aid of cathodic polarization curves. It has been observed that volume fraction of martensite have definite influence on the corrosion behaviour of dual-phase steel. As a result of this study, it is found that corrosion rate of dual-phase steel has increased with increase volume fraction of martensite.
Keywords: Corrosion; Dual-phase; Martensite; Concrete